Numerical and experimental investigations on micro-detonation of striking arc machining of alumina. (June 2014) - Zhang, Baoguo; Tian, Xinli; Wang, Wanglong; Tang, Xiujian; Wang, Pengxiao
Numerical and experimental investigations on micro-detonation of striking arc machining of alumina ceramics were performed to ascertain the material removal mechanism and study the effects of the process parameters on the machining performance. The shape of the micro-detonation plasma jet and the ablation pit generation process were observed by high-speed video and machining test. A three-dimensional finite element model for temperature simulation during a single-pulse micro-detonation of striking arc machining process was developed and validated by corresponding experiments. The effects of the five process parameters, that is, working current, gas pressure, pulse width, nozzle stand-off distance, and muzzle diameter, on the highest temperature and material removal rate were studied by employing the Taguchi method. The findings indicated that the simulated results were in good agreement with the experiments. The material removal mechanism for alumina machined by micro-detonation of striking arc machining was determined based on high-speed video observation, numerical simulation, and experimental study. The alumina ceramics were mainly removed by a combination of sublimation, melting, and phase transformation under the synergistic effect of high temperature and high impact force of the micro-detonation plasma jet. The highest temperature and the material removal rate were significantly affected by the process parameters. Both temperature and material removal rate increased with increase in the working current, gas pressure, and pulse width, but decreased with the increase in the nozzle stand-off distance and nozzle diameter. Based on the analysis of variance and the effects of parameters on the highest temperature and material removal rate, the optimal combination of parameters was presented. This study may serve as a reference in understanding the machining mechanism of micro-detonation of striking arc machining and presents a method that can be used for efficient machining of alumina.